A static approach to the Nelson-Siegel-Svensson model : an application for several negative yield cases - Garcia, Maria Teresa (2018)
The appearance of negative bond yields presents significant challenges for the fixed income markets, which mainly concern related forecasting models. The Nelson-Siegel-Svensson model (NSS) is one of the models that is most frequently used by central banks to estimate the term structure of interest rates. The objective of this study is to evaluate the application of the NSS model to fit the yield curve of a set of 20 countries, the majority from the Eurozone, which registered negative sovereign bond yields. We conclude that the model adjusted well for all countries’ yield curves, although no changes or constraints were introduced. In addition, a comparison was carried out between market instantaneous interest rate and the interest rate for the very distant future, which the model can predict, with good results for the instantaneous interest rate. An evaluation of the possible behaviour of shared debt securities (i.e. Eurobonds) was also analysed. In conclusion, the NSS model seems to remain a valuable, easy to use, and adaptable tool, to fit negative yield curves, for monetary policy institutions and market players alike.